Natural unblinding of BCG vaccination trials. Issue 15 (8th April 2021) - Szigeti, Reka; Kellermayer, Richard
Graphical abstract: Abstract: There is significant public and clinical interest in the potential for Bacillus Calmette-Guérin (BCG) vaccination to protect against type 2 Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV-2) induced COVID-19. This question could be best answered by blinded and placebo controlled clinical trials. However, a skin reaction occurs within days at the site of BCG injection, making it rather challenging to blind this vaccination. Here, we examined registered clinical trials in ClinicalTrials.gov on BCG against COVID-19 by October 9th 2020, and found that 94.7% of such trials were listed as placebo controlled (all with normal saline as placebo), and single to quadruple blinded. The mode of overcoming the natural unblinding by the BCG induced skin reaction was not clarified on the website in either of the trials. We conclude that detailed description of the strategy towards overcoming the BCG vaccination induced skin reaction associated unblinding hurdle will be important for the interpretation of the theoretically blinded COVID-19 directed clinical trials.